Liquidity, Return on Assets And Sales Growth on Tax Avoidance With Firm Size as Intervening Variables in Banking Companies Listed in Indonesian Stock Exchange Between 2017-2021 - Ronni Andri Wijaya; Ramdani Bayu Putra; Hasmaynelis Fitri; Lubis, Maulana Arif (Research Horizon, 2022)
This study aims to examine the effect of liquidity, return on assets, sales growth on tax Avoidance through firm size as an intervening variable. Liquidity, return on assets, and sales growth are used as independent variables and tax Avoidance as the dependent variable. And the size of the company as an intervening variable. This research was conducted on banking companies listed on the Indonesia Stock Exchange (IDX) in 2017-2021. The sample selection in this study used purposive sampling method so that from 45 populations a sample of 30 companies was obtained. The data in this study were analyzed using panel data regression analysis techniques. The results of this study indicate that return on assets and firm size have a significant effect on tax Avoidance, while liquidity and sales growth have no significant effect on tax Avoidance. Liquidity has a significant effect on firm size, while return on assets and sales growth have no effect. Company size was successful in mediating the effect of liquidity on tax Avoidance, but not for return on assets and sales growth.